Micro Machining Process Selection: An Integrated Theory. (2016) - Kuriakose, Sandeep; Mangalan, Anil Varghese; Namboothiri, Babu; Ray, Amitava
Abstract: Selection of most apposite machining method is very crucial in precision machining of micro parts. Micro machining has wide applications in the fabrication of micro-electro-mechanical systems (MEMS), micro- fluidics and precision surgical instruments. The machining processes for these diverse applications have to be selected based on different accuracy attributes combined with least operating cost. So formulation of an appropriate selection methodology is very decisive. The aim of this paper is to develop a methodology for machining process selection by comparing the various attributes. An integrated approach combining technique for order preference by similarity to ideal solution (TOPSIS) & analytic hierarchy process (AHP) have been proposed. A case study has been presented to select from the major nontraditional machining processes for the purpose of micro drilling of fuel injector nozzle hole of specific diameter ranges by comparing their various attributes. The research shows that the methodology TOPSIS integrated with AHP is a very effective technique in selection of machining process based on applications by considering different attributes.